PENGEMBANGAN MEDIA PEMBELAJARAN POP-UP BOOK PADA MATERI KEBERAGAMAN DI PEGUNUNGAN BINTANG UNTUK MENINGKATKAN LITERASI BUDAYA SISWA SMP - Tinus Keromen; Dionisius Heckie Puspoko Jati; Nani Mediatati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Indonesia is an archipelagic country that has a very diverse cultural and ethnic wealth. This development research aims to develop instructional media in the form of a Pop-Up Book on cultural diversity material in Bintang Mountains Regency for junior high school students. This study follows the Borg and Gall development model which has been modified into seven main stages: potentials and problems, data collection, initial product design, design validation, design revision, limited testing, and final revision. The validation results from material experts showed a feasibility level of 90%, while media experts gave a score of 88%. The limited trial involving 18 seventh-grade students showed a very positive response, where 94% of students stated the media was attractive, 92% felt it was easier to understand the material, and 90% felt motivated to learn. Thus, the Pop-Up Book learning media is proven to be effective as a learning aid that can increase learning interest, clarify abstract concepts, provide contextual learning experiences, and serve as a means of preserving local culture.